Phantom Limb Pain: A Systematic Neuroanatomical-Based Review of Pharmacologic Treatment. Issue 2 (13th February 2014) - McCormick, Zachary; Chang-Chien, George; Marshall, Benjamin; Huang, Mark; Harden, R. Norman
Abstract: Objective: Review the current evidence-based pharmacotherapy for phantom limb pain (PLP) in the context of the current understanding of the pathophysiology of this condition. Design: We conducted a systematic review of original research papers specifically investigating the pharmacologic treatment of PLP. Literature was sourced from PubMed, Embase, Scopus, and the Cochrane Central Register of Controlled Trials (CENTRAL). Studies with animals, "neuropathic" but not "phantom limb" pain, or without pain scores and/or functional measures as primary outcomes were excluded. A level of evidence 1–4 was ascribed to individual treatments. These levels included meta-analysis or systematic reviews (level 1), one or more well-powered randomized, controlled trials (level 2), retrospective studies, open-label trials, pilot studies (level 3), and anecdotes, case reports, or clinical experience (level 4). Results: We found level 2 evidence for gabapentin, both oral (PO) and intravenous (IV) morphine, tramadol, intramuscular (IM) botulinum toxin, IV and epidural Ketamine, level 3 evidence for amitriptyline, dextromethorphan, topiramate, IV calcitonin, PO memantine, continuous perineural catheter analgesia with ropivacaine, and level 4 evidence for methadone, intrathecal (IT) buprenorphine, IT and epidural fentanyl, duloxetine, fluoxetine, mirtazapine, clonazepam, milnacipran, capsaicin, and pregabalin. Conclusions: Currently, the best evidence (level 2) exists for the use of IV ketamine and IV morphine for the short-term perioperative treatment of PLP and PO morphine for an intermediate to long-term treatment effect (8 weeks to 1 year). Level 2 evidence is mixed for the efficacy of perioperative epidural anesthesia with morphine and bupivacaine for short to long-term pain relief (perioperatively up to 1 year) as well as for the use of gabapentin for pain relief of intermediate duration (6 weeks).